Lexical features of diplomatic units found in the documents of the era of the Ottoman Empire - Бегимовa Г. A.; Кенжaлин Қ. К. (Journal of Oriental Studies, 2017)
History of diplomatic documents, written in Turkish, ancient. The letters in the Turkish language, written in the distant past, have survived to this day. The texts, written in the time of the Ottoman Empire, of sufficient quality, in the field of linguistic theory harmoniously structure composition and grammatical base. The order of words in a sentence of the time saved in the modern Turkish language. The article discusses the diplomatic units, found in documents written during the Ottoman Empire. Studied each diplomatic unit, the definition of each word.